Pengaruh Word Of Mouth dan Product Quality terhadap Kepuasan Pelanggan dengan Harga sebagai Variabel Moderasi : (Survei pada Pelanggan Omah Wedangan di Mojosongo Surakarta) - Khollilu Rohman; Sumaryanto Sumaryanto; Retno Susanti (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The purpose of this study was to determine the effect of the significance of word of mouth and product quality on customer satisfaction with price as a moderating variable on Omah Wedangan customers in Mojosongo Surakarta. Quantitative research type. The data sources used are primary data and secondary data. The sampling technique in this study used purposive sampling technique, which is a sampling determination technique with certain considerations. The number of samples used in this study was 100 respondents. The instrument testing technique used validity and reliability tests, classical assumption tests consisting of multicollinearity tests, autocorrelation tests, heteroscedasticity tests and normality tests. The data analysis technique used in this study was descriptive analysis, multiple linear regression analysis with moderating variables, t-test, F-test, and R2 test and moderation test. The results of this study indicate that the t-test obtained a ρ-value (significance) = 0.003 <0.05, meaning that word of mouth has a significant effect on Y (customer satisfaction). The ρ-value (significance) = 0.000 <0.05 means that product quality has a significant effect on Y (customer satisfaction. The ρ-value (significance) = 0.000 <0.05 means that price has a significant effect on Y (customer satisfaction). The F test shows an F count value of 207.158 with a significance value (p.value) of 0.000 <0.05, meaning that the model is right in predicting the effect of X1 (word of mouth), X2 (product quality) and Z (price) on Y (customer satisfaction). The results of the determination coefficient test (adjusted R Square) are 0.862, meaning that the amount of contribution of the influence of the independent variables X1 (word of mouth), X2 (product quality) and Z (price) is 86.2%. The rest (100% - 86.2%) = 13.8% is explained by other variables outside the model, such as location, service, comfort and cleanliness. Test results moderation 1 (b) is negative, meaning that price weakens the influence of word of mouth on customer satisfaction. The significance value (p-value) of the interaction X1Z (moderation 1) = 0.071 > 0.05 is obtained, meaning that price does not moderate the influence of word of mouth on customer satisfaction. Moderation 2 (b) is negative, meaning that price weakens the influence of product quality on customer satisfaction. The significance value (p-value) of the interaction X2Z (moderation 2) = 0.003 < 0.05 is obtained, accepted, meaning that price moderates the influence of product quality on customer satisfaction at Omah Wedangan in Mojosong Surakarta.